2012
DOI: 10.1111/j.1463-6395.2012.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term injection of dopamine on the ovarian growth of Cherax quadricarinatus juvenile females (Parastacidae, Decapoda)

Abstract: The neurotransmitter dopamine (DA) modulates many physiological processes in decapod crustaceans, including reproduction. This study was aimed at evaluating whether the long‐term injection of DA affects ovarian growth in the freshwater crayfish Cherax quadricarinatus. Three experiments were performed with females of different mean initial size: 4.15 g (Group A); 9.65 g (Group B); and 13.98 g (Group C). Treated females were injected with DA and control females with physiological saline twice a week for 90 (Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The morphological, histological and biochemical parameters used for assessing ovarian maturity clearly indicated that 5-HT had a stimulatory effect while DA had the opposing effect. The 5-HT induced and DA inhibited gonadal maturation have been reported in a number of decapods (Richardson et al, 1991;Sarojini et al, 1995a;Vaca & Alfaro, 2000;Chen et al, 2003;Alfaro et al, 2004;Wongprasert et al, 2006;Santhoshi et al, 2009;Tinikul et al, 2009;Sainath & Reddy, 2011;Tropea & Lopez Greco, 2013;Aprajita et al, 2014;Prasad et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The morphological, histological and biochemical parameters used for assessing ovarian maturity clearly indicated that 5-HT had a stimulatory effect while DA had the opposing effect. The 5-HT induced and DA inhibited gonadal maturation have been reported in a number of decapods (Richardson et al, 1991;Sarojini et al, 1995a;Vaca & Alfaro, 2000;Chen et al, 2003;Alfaro et al, 2004;Wongprasert et al, 2006;Santhoshi et al, 2009;Tinikul et al, 2009;Sainath & Reddy, 2011;Tropea & Lopez Greco, 2013;Aprajita et al, 2014;Prasad et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, in M. rosenbergii, 5-HT-treated group exhibited significantly greater OI and mean OD values with more number of vitellogenic and mature oocytes (Meeratana et al, 2006) and accelerated vitellogenin synthesis (Kuo et al, 2009) whereas the DA-treated group displayed diminished vitellogenin synthesis (Chen et al, 2003). It was reported that in Cherax quadricarinatus, DA treatment effected decreased OI values with a higher percentage of underdeveloped ovaries (Tropea & Lopez Greco, 2013). In M. rosenbergii, Reddy et al (2013) observed that 5-HT administration boosted the total lipid and triglyceride contents of the ovary and hepatopancreas while contradictory results were obtained with DA.…”
Section: Discussionmentioning
confidence: 99%
“…The primary (or pre-vitellogenic) oocytes were identified by a homogeneous and acidophilic cytoplasm surrounded by round basophilic follicular cells. In contrast, secondary oocytes had an eosinophilic cytoplasm containing yolk droplets and globules, and were surrounded by flat and pyknotic follicular cells [34].…”
Section: Methodsmentioning
confidence: 99%